223Ra-chloride therapy in men with hormone-refractory prostate cancer and skeletal metastases: Real-world experience. Issue 2 (March 2018) - Boni, Giuseppe; Mazzarri, Sara; Cianci, Claudia; Galli, Luca; Farnesi, Azzurra; Borsatti, Eugenio; Bortolus, Roberto; Fratino, Lucia; Gobitti, Carlo; Lamaj, Elda; Ghedini, Pietro; Rizzini, Elisa Lodi; et al.
Background: Radium-223 ( 223 Ra) chloride, an alpha emitter, has been shown to improve overall survival (OS) and pain control, and to delay skeletal-related events, in patients with castration-resistant prostate cancer (CRPC) and bone metastases. Our retrospective observational study presents the first Italian experience on the efficacy and safety of 223 Ra therapy in routine clinical practice. Methods: A total of 83 patients with metastatic CRPC were treated with 223 Ra at 3 Italian centers between August 2013 and August 2016. 223 Ra-chloride (55 kBq/kg) was administered every 4 weeks for a total of 6 cycles. Primary endpoints were OS and progression-free survival (PFS). Secondary endpoints included toxicity, pain evaluation using numeric rating scale (NRS), symptomatic skeletal-related events and biomarkers response. Results: Patients had a median age of 75 (range 53–89) years. The majority of men showed a Gleason score of 7, 8, or 9. Forty-one patients completed 6 treatment cycles; 33 stopped treatment before completing 6 cycles. Nine were still receiving therapy at the time of data collection. At the end of therapy, NRS pain scores significantly improved ( p < .000001). OS was a mean of 10.1 months, while median OS had not been attained. According to Kaplan-Meier estimation, OS and PFS were 17.5 and 7.7 months, respectively. There was a significant correlation between OS and PFS with the number of 223 Ra cycles; patients receiving all 6 cycles experienced the major benefit from the therapy. 223 Ra was well-tolerated. Conclusions: 223 Ra alpha therapy is an important therapeutic option for men with CRPC and symptomatic skeletal metastases.